PATTERNS FOR HANDLING EROSION HAZARDS AND LAND CRITICALITY IN THE BAUMATA WATERSHED IN KUPANG DISTRICT - Lasmana, Indradhi; Ambrosius Raha Lelang Wayan; Yohana Milo (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2024)
Baumata watershed is located in Kupang district. The land use conditions are mostly forests, paddy fields, with low root depth and play a major role in the process of causing soil damage, accelerating the rate of erosion and increasing the volume of surface runoff. This research examines the current level of erosion hazard in the existing land use of the Baumata Watershed and its area by considering the Regional Spatial Planning (RTRW) of Kupang Regency and its surroundings in the Baumata Watershed. The method used to calculate the rate of erosion is the MUSLE method where the method uses an approach from the surface runoff factor. The data processing uses a Geographic Information System (GIS). The erosion rate watershed is 3,402,685 tons/ha/year with a watershed area of 2,439.35 ha. Land rehabilitation and soil conservation (ARLKT) directions that are appropriate for the conditions of the Baumata watershed are 87 annual crop cultivation areas. 21 % (2,127.42 ha), Seasonal Plant Cultivation Areas 10.67 % (260.38 ha), and Buffer Areas 2.11 % (51.55 ha). The existence of data and information on the magnitude of erosion rates and land criticality in the Baumata watershed in Kupang district can be used to anticipate early landslide disasters in the area. Keywords: Erosion; Land Criticality; MUSLE; GIS.